Upaya Penegakkan Hak Bertemu Anak Bagi Orang Tua Non Pemegang Hadhanah Pasca Perceraian - Fadil Sidik Fatahilah; Prahasti Suyaman (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2025)
Divorce often creates new problems, one of which is related to child custody and visitation rights for parents who do not have custody. Prohibiting visitation by the custodial parent not only violates the rights of the non-custodial parent, but also disregards the child's right to receive affection from both parents. The purpose of this study is to examine the types of legal protection available to non-custodial parents who are prohibited from seeing their children. This study uses a normative legal research method with a statutory approach. Data collected from interviews with legal practitioners and parties who have experienced similar problems are included in this study. The results show that prohibiting parents who have custody from meeting their children is against the law and contrary to the principle of the best interests of the child. Parents who do not have custody rights can file a lawsuit to revoke custody rights, as stipulated in SEMA No. 1 January 2017. This study emphasizes the importance of the law in balancing the rights and obligations of parents after divorce for the best interests of the child.